"Selling Fire to the Devil": Commentary on Danielle Knafo's "The Sexual Illusionist". Issue 1 (2nd January 2020) - Elise, Dianne
Abstract : This paper discusses the pain of oedipal exclusion, especially in relation to the felt loss of the maternal figure. When too acute, this loss may be defended against by omnipotent defenses of disavowal and evasion of reality—a perverse structuring of the mind. In clinical work with such a person as an adult, sexualization of the dyadic treatment relationship within the analytic field serves to avoid deeper feelings of loss and deflated self-esteem. Mourning is foreclosed, and impasse may result. If "love" is to effect a cure, it is not "romantic" love of the analyst, but love of the analytic process—a passionate inquiry into the self. When fully articulated as an energy potential in both participants, analytic eroticism can offer libidinal engagement within an ethical frame as a stimulus to emotionally embodied thinking that can yield transformations in many dimensions, including the erotic.